ANALISIS FINANSIAL DIVERSIFIKASI PRODUK KELAPA MENJADI VCO (Virgin Coconut Oil) DENGAN METODE EMULSI - Imaculata Fatima (Agriculture Faculty of Flores University, 2008)
Coconut plant is a plant that grows in a tropical area. It dominates growing in the coastal area. Ende Regency is a part of the district, located in East Nusa Tenggara Provence particularly in Flores island. The plan is one of the commodities in Ende that support it increase the income of the people generally. However, coconut is relatively low. For instance, one fruit is five hundred or a thousand rupiah. In reality, each plant of coconut can produce 25-30 fruits every month (APCC, 2004). Most of the coconut plants in Ende is a kind of local coconut which is known